Structural and electronic properties of perovskite hydrides ACaH3 (A=Cs and Rb) - Lamichhane, S; Aryal, B; Kaphle, GC; Adhikari, NP (BIBECHANA, 2015)
We have performed structural properties, electronic properties, charge density and potential distribution of CsCaH3 and RbCaH3 using TB-LMTO-ASA approach under local density approximation.  Our findings show that both CsCaH3 and RbCaH3 are non-magnetic and then insulators with estimated direct band gaps (M-M) of 3.15 eV and 3.17 eV respectively. Our estimated values of band gap suggest to both materials as better candidate for the high frequency ultra-violet devices. Furthermore, role of corner atoms in perovskite hydrides are also presented in this study. Present calculations agree well with the previous work.BIBECHANA 13 (2016) 94-99